Tamoxifen and residual tumor volume in postoperative nonfunctioning pituitary neuroendocrine tumors: a pilot study - Haydar Ali Tajuddin, Amalina; Sukor, Norlela; Azizan, Elena Aisha; Kamaruddin, Nor Azmi; Omar, Ahmad Marzuki; Tan, Geok Chin; Mustangin, Muaatamarulain; Mohamed Mukari, Shahizon Azura; Alias, Azmi; Abd Latif, Kartikasalwah; Tay, Poh Sen; Kasim, Fauziah; et al. (Japan Endocrine Society, 2024)
Selective anti-estrogen receptor modulators (SERMs) have been shown to reduce the size of pituitary tumors. However, their clinical effect on nonfunctioning pituitary neuroendocrine tumors (NF-PitNET) in humans has not yet been established. We conducted a randomized controlled trial of tamoxifen versus conservative treatment in postoperative patients with residual tumors positive for estrogen receptor immunostaining to investigate the potential clinical impact on tumor volume. In this pilot study of 16 NF-PitNET patients, eight patients were randomized to receive 20-40 mg of tamoxifen daily for six months, while the other eight patients were treated conservatively. Serial MRI scans of the pituitary gland were performed at the beginning and end of the six months. Tamoxifen led to a significant reduction (> 25%) in tumor volume in three patients, while the tumor stabilized in the remaining five patients (p=0.046). In the control group, significant tumor growth was observed in three patients, while no significant change in tumor volume was observed in the remaining five patients. In general, tamoxifen was well tolerated. This pilot study illustrates the potential role of tamoxifen in postoperative residual NF-PitNET. This response to tamoxifen therapy needs to be further investigated in a longer-term study with a larger number of patients.